Evaluasi Program Pemberian Kudapan pada Balita yang Mengalami Masalah Pertumbuhan di Kota Surabaya Tahun 2023: Evaluation of the Snack Distribution Program for Toddlers with Growth Problems in Surabaya City in 2023 - Tiffany Hadi Jaya; Lailatul Muniroh; Wanda Aisyah Rahmaniasari (Universitas Airlangga, 2025)
Background: The prevalence of malnutrition among toddlers in Surabaya is 4.8% for stunting and 6.1% for wasting. Therefore, the City Government implemented a snack distribution program targeting toddlers with growth problems. Given the importance of this nutrition intervention, an evaluation is needed to assess its implementation and effectiveness. Objectives: This study aims to evaluate the implementation of the snack distribution program for toddlers with stunting, pre-stunting, and malnutrition in Surabaya City in 2023. Methods: This qualitative evaluation involved in-depth interviews with City Health Office staff, nutritionists at community health centers (puskesmas), and mothers of target toddlers, as well as document analysis conducted from June to July 2024 at the City Health Office and five puskesmas in Surabaya City. Data was collected using structured questionnaires and relevant documents. Qualitative data was analyzed using thematic analysis. Results: The evaluation revealed several problems, such as a shortage of nutritionists and incomplete program mechanisms. Snack consumption among toddlers was inconsistent because some of them did not receive snacks or received snacks that were unfit for consumption due to the negligence of Micro, Small, and Medium Enterprises (MSMEs). In addition, snack acceptance was low due to differences in toddlers’ preferences. Five out of 15 toddlers showed improved growth indicators and a downward trend in the prevalence of stunting, pre-stunting, and malnutrition; however, the overall program implementation remained suboptimal. Conclusions: The snack distribution program for toddlers with growth problems in Surabaya City in 2023 has not yet been implemented optimally. Systematic and strategic improvement is required to improve the program’s effectiveness and results.